Pseudogene AC106872.1 is involved in maintaining the self-renewal capacity of human embryonic stem cells - JIANG Zhengyang, SUN Mengyao, HE Liu, YU Jia, MA Yanni (Jichu yixue yu linchuang)
Objective To explore the role of pseudogene AC106872.1 in maintaining the self-renewal capacity of human embryonic stem cells (hESCs). Methods AC106872.1 was knocked out in hESCs and knockout efficiency was validated by PCR and agarose gel electrophoresis. The colony formation of hESCs was assessed through colony formation assays and alkaline phosphatase (AP) staining. The expression level of pluripotency and differentiation marker genes was analyzed by qPCR and flow cytometry. RNA sequencing (RNA-seq) was performed to assess transcriptomic changes upon AC106872.1 knockout. Results Knockout of AC106872.1significantly inhibited the colony formation of hESCs (P＜0.05). The expression level of pluripotency marker genes was significantly reduced (P＜0.000 1), while the expression of differentiation marker genes was markedly increased (P＜0.000 1). Conclusions The pseudogene AC106872.1 plays a crucial role in maintaining human embryonic stem cell self-renewal through regulation of pluripotency genes expression.